Biological and molecular diagnostic methods in breast cancer Part II. Profiling and imaging of biological processing - Ślubowski, Tadeusz; Ślubowska, Małgorzata; Kujawa, Marek (Contemporary Oncology/Współczesna Onkologia, 2007)
This review describes molecular diagnostic techniques, real time in vivo imaging as well as markers for mixed molecular-imaging methods. It presents molecular mapping differentiating malignant changes on the basis of aberrant gene expression and/or changes in proteins, helping to identify early stages of the disease, its development and targeted treatment at the molecular level. It presents real time imaging of glucose metabolism, oxygen utilization and blood flow in cancer tissue. Signal amplification in cell cycle regulation, multidrug resistance, angiogenesis, apoptosis, mapping via cancer-specific signal emitters, functional imaging by molecular markers, along with positron emission tomography PET, as well as photon emission tomography and methods combining use of antibodies and the protein compounds for MRI to display cancer membrane antigens and apoptotic proteins are also described. Finally, it elucidates photoimaging utilizing bioluminescent and fluorochrome near-red markers, as well as fluorescent “red-shift” protein markers.